EFFECT OF VERBAL SYMBOLISING- TECHNIQUE ON PRIMARY ONE PUPILS’ ABILITY TO READ AND WRITE YORUBA (1985)
The purpose of this investigation was to discover the different advantages of using verbal symbolising technique (V. S. T.) and the traditional phonic/syllabication method (P.S.M) for introducing similar groups of primary one pupils to initial literacy in Yoruba language. The influence of other factors such as age, sex and home background on the functioning of V. S. T. and P. S.M. was also considered. To this effect, a pre-test-post-test experimental design was used in the study. The study sample consisted of 162 primary one pupils from 4 selected schools and 45 primary one teachers from 12 selected schools in Oyo - a typical Yoruba town in Oyo State of Nigeria. A teacher opinion questionnaire (T.Q), a home background questionnaire (H.B.Q.), and a battery of the Yoruba language achievement tests (APOYTA) were the major instruments used for the study. The T. Q. was administered on the selected primary one teachers to obtain data in respect of age, sex and qualification. It also sought the teachers’ opinion about the existing primary one classroom environments; methods and primers for teaching Yoruba to primary one pupils. The H.B.Q was administered to the selected primary one pupils to obtain data on the age, sex and home environment of the learners. The APOYTA was designed to measure Yoruba language achievement at the primary one level and it consists of five sub-tests. (i) Recognition and writing of letters of the alphabet; (ii) Combining letters to form words; (iii) Recognition and writing of words; (iv) Reading of words and simple sentences; (v) Writing of simple words. Data obtained from the questionnaires and Yoruba language achievement test scores were analysed, using the following methods. (1) t. test of significance; (2) Two way analysis of variance; (3) Pearson Product Moment Correlation; (4) Descriptive statistics in form of frequencies and percentages. The results revealed that pupils taught with the V.S. T. seem superior to those taught with the P. S. M. in ability to read and write Yoruba at the end of their first year in school. Age, sex and home background did not disturb the positive performance of pupils who were taught through the V. S. T. Whereas, the home background had significant influence on the performance of pupils who were taught through the P. S.M. The teachers in both the experimental and control groups had similar characteristics. The environmental conditions of the classrooms were the same for both groups. The use of relevant primer, adequate scheme of work, explicit teachers’ guide, sufficient teaching/learning aids and pupils’ practice exercises through the workbook in the V.S.T. was the probable cause of the significant difference in pupils’ performance favouring the experimental group. Perhaps this is why the regular teachers of primary one pupils are of the same opinion with the present researcher that a change is necessary in the existing method and primer used to teach initial literacy in Yoruba to young children.